Compounds with Polar Metallic Bonding - Hoch, Constantin (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Edition 'Compounds with Polar Metallic Bonding' is a collection of eight original research reports presenting a broad variety of chemical systems, analytical methods, preparative pathways and theoretical descriptions of bonding situations, with the common aim of understanding the complex interplay of conduction electrons in intermetallic compounds that possess different types of dipoles. Coulombic dipoles introduced by electronegativity differences, electric or magnetic dipoles, polarity induced by symmetry reduction-all the possible facets of the term 'polarity'-can be observed in polar intermetallic phases and have their own and, in most cases, unique consequences on the physical and chemical behaviour. Elucidation of the structure-property relationships in compounds with polar metallic bonding is a modern and growing scientific field which combines solid state physics, preparative chemistry, metallurgy, modern analytic methods, crystallography, theoretical calculations of the electronic state and many more disciplines.